Hubungan Dukungan Sosial dengan Tekanan Darah pada Penderita Hipertensi di Puskesmas Kembaran I Kabupaten Banyumas - Arinda Hanza Tiwi; Pramesti Dewi; Etika Dewi Cahyaningrum (Poltekkes Kemenkes Bengkulu, 2022)
Hypertension is a condition where blood pressure > 140/90 mmHg. Low social support can affect the occurrence of hypertension. Because people with hypertension will be more motivated to do treatment if they get support from those closest to them .This study aims to determine the correlation between social support and blood pressure on hypertensive patients in Kembaran I Community Health Center Banyumas Regency. This type of research is quantitative with a cross-sectional study design and sampling technique in this study was purposive sampling with a total of 116 respondents. The research instrument used to measure social support is the Multidimensional Scale of Perceived Support questionnaire. The results showed that most of the respondents had social support as many as 48 respondents (41.4%) with hypertension grade I. The results of the Sperman Rank test obtained a p-value of 0.001 <0,05 which means that there is a significant correlation between social support and blood pressure on hypertensive patients in Kembaran I Community Health Center Banyumas Regency with a Correlation Coefficient (CC) of 0.537. The higher the social support, the lower blood pressure in hypertension. The study is expected to add knowledge to respondents about the importance of controlling blood pressure and for families to provide more social support and monitoring of sick family members.